Social determinants of health and dual sensory loss in older adults: A scoping review - Abinethaa Paramasivam; Ved Hatolkar; Renu Minhas; Aswen Sriranganathan; Pineal Bareamichael; Atul Jaiswal; Walter Wittich (PLoS ONE, 2025)
Background Social determinants of health (SDH), such as socioeconomic status, education, healthcare access, and social support, play a significant role in shaping individuals lived experiences. Dual sensory loss (DSL), a distinct disability involving both vision and hearing loss, poses greater challenges for daily living compared to the general population. This scoping review synthesized evidence on how various SDH indicators influence the life experiences of older adults with DSL. Methods Five scientific databases were searched from January 2014 to May 2024. Articles focusing on individuals aged 60 and older with DSL, in the context of at least one SDH indicator, were included. Results A total of 69 studies met the eligibility criteria. Most studies addressed the following SDH indicators: disability (n = 46), social inclusion and non-discrimination (n = 21), gender (n = 10), and access to healthcare services (n = 9). Disability-related indicators revealed higher risks of mobility limitations, cognitive decline, depression, anxiety, social isolation, and workplace discrimination, all adversely affecting mental health and quality of life. Older adults with DSL encounter significant barriers to accessing healthcare, such as absence of adequate assistive devices, communication challenges, and high healthcare costs. Many report dissatisfaction with the quality of care received. Conclusions Our review identifies disparities that increase the vulnerability of older adults with DSL and restrict their access to healthcare, rehabilitation, and social participation. These findings warrant further research on underexplored SDH factors, using robust data sources that collects information on the lived experiences of older adults with DSL. Addressing these social determinants requires a comprehensive approach, including raising awareness, improving service access, enhancing social support networks, and ensuring inclusive policies and practices.